FRI0067 Prognostic factors for rapid radiographic progression are different between tnf and non-tnf inhibitor. (23rd January 2014) - Katayama, K.; Sato, T.; Okubo, T.; Fukai, R.; Ito, H.
Abstract : Background: The cause of the Rapid Radiographic Progression (RRP) is still unclear, and RRP is resistant to any biological treatment. Many prognostic factors including clinical and serologic marker, ultrasound and MRI findings have been reported for RRP rheumatoid arthritis (RA) patients treated by non-BIO and BIO DMARDs. We have also reported that perpetuations of bone marrow edema in MRI are predictor for RRP in RA patients treated with adalimumab (1). Meanwhile, there have been few reports about comparison between prognostic factors for TNF and non-TNF inhibitors in RRP patients. Objectives: To analyze prognostic factors for RRP RA patients treated 1 year with tocilizumab (TCZ: non-TNF inhibitor) and adalimumab (ADA: TNF inhibitor). Methods: Modified total sharp score (mTSS) were assessed to find RRP (ΔmTSS/year>3). DAS28-ESR, HAQ-DI, CRP, ESR, MMP3, RF, anti-CCP antibody were measured. The chi-squared test and the Wilcoxon test were used for the statistical analysis. Results: The baseline characteristics (mean values) for TCZ and ADA groups were: age: 58.8 vs 60.9 years, disease duration: 84.4 vs 110.7 months, pre-trial biological treatment: 60% vs 2%, concomitant MTX use: 72% vs 91%, DAS28-ESR: 6.24 vs 6.04, HAQ-DI: 1.78 vs 1.73, mTSS: 65.7 vs 65.4, mTSS/y before TCZ treatment: 10.1 vs before ADA treatment:11.4, MMP-3: 513 ng/ml vs 384 ng/ml, and CRP: 6.42 mg/dl vs 2.92 mg/dl (P<0.01). DAS28-ESR, HAQ-DI, Δm TSS/year 1 year after TCZ and ADA treatment were 3.79 and 3.57, 1.22 and 1.02, and 2.91 vs -0.69, respectively. No apparent significance in baseline clinical data was observed between bio-naïve and TNF pre-treated RA patients in TCZ treated patients. After 1 year TCZ treatment, 8 patients were in RRP group (ΔmTSS/y: 10.7) and 17 patients were in non-RRP group (ΔmTSS/y: -0.75). After 1 year ADA treatment, 7 patients were in RRP group (ΔmTSS/y: 7.24) and 39 patients were in non-RRP group (ΔmTSS/y: -2.15). Among baseline clinical factors in TCZ treated RA patients, serum CRP level (9.5mg/dl vs 5.0 mg/dl, p=0.045) and mTSS/year (14.9 vs 7.9, p=0.003) were significantly increased in RRP group compared with non-RRP group. Swollen joint count (SJC) had weak trend in RRP group at baseline (p=0.056) and 1 year after treatment (p=0.056). On the other hand, no statistically significant difference was observed in baseline serum CRP level (p=0.27), mTSS/year (p=0.39), SJC (p=0.67) between ADA treated RRP and non-RRP groups. Among baseline clinical factors in ADA treated patients, baseline serum MMP-3 (651 ng/ml vs 332.4 ng/ml, p=0.012) was significantly increased in RRP group compared with non-RRP group. Decrease in ΔDAS28-ESR (p=0.054), increase in VAS at 12 mo (p=0.063) and MMP-3 at 12 mo (p=0.063) had weak trend in ADA treated RRP group. On the other hand, no significance was observed in baseline MMP-3 (p=0.19), Δ DAS28-ESR (p=0.34) between TCZ treated RRP and non-RRP group. Conclusions: Prognostic factors for RRP in TCZ and ADA were different -baseline CRP, mTSS/year, S.J.C for TCZ, baseline MMP-3, ΔDAS28-ESR for ADA. References: Katayama, K et al. (2012). Ann Rheum Dis 71, supple. 3, 504 Disclosure of Interest: None Declared